Potensi dan Praktik Literasi Artificial Intelligence (AI) dalam Pendidikan Anak Usia Dini di Indonesia: Systematic Literature Review - Khosibah, Salma Aulia; Rahmaningrum, Afifah; Kusumawardani, Cindy Tri (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2025)
The rapid development of Artificial Intelligence (AI) has significantly impacted various sectors, including Early Childhood Education (ECE). This study aims to identify the potential and current practices of AI literacy within the context in Indonesia and emphasizes the importance of strengthening AI literacy from an early age to prepare a generation that is adaptive to technology. A Systematic Literature Review (SLR) was conducted using the PICO framework and PRISMA protocol. Literature was systematically collected from Google Scholar, ScienceDirect, Springer, and Sinta, resulting in 79 articles, of which 14 met the inclusion criteria (Indonesian-based studies, published between 2020–2025, in Indonesian or English). The data were then analyzed using thematic analysis. Findings indicate that AI literacy has a strong potential to enhance learning quality in ECE through interactive, adaptive, and personalized approaches. Technologies such as chatbots, augmented reality (AR), and virtual reality (VR) have been utilized to support cognitive, social-emotional development, and children with special needs. However, AI practices in Indonesia remain limited to institutions with adequate digital infrastructure and technologically literate educators. The lack of empirical research also highlights the need for further exploration. Optimizing AI implementation requires multi-stakeholder collaboration to strengthen infrastructure, train educators, and develop policies that prioritize ethics, safety, and equitable access before national scaling.